Optimization of ultrasonographic examination for the diagnosis of erosive Rheumatoid Arthritis in comparison to erosive hand Osteoarthritis. Issue 118 (September 2019) - Roux, Camille; Gandjbakhch, Frédérique; Pierreisnard, Audrey; Couderc, Marion; Lukas, Cédric; Masri, Racha; Sommier, Jean-Philippe; Clerc-UrmeS, Isabelle; Baumann, Cédric; Chary-Valckenaere, Isabelle; Loeuille, Damien
Abstract: Objective: to determine thresholds and better scenario for the diagnosis of erosive rheumatoid arthritis (RA) by ultrasonography (US) in RA in comparison to osteoarthritic (OA) patients. Methods: Patients, prospectively included, fulfilling ACR 1987; ACR/EULAR 2010 criteria for RA or hand OA criteria. Radiographic assessment (RX): Sharp erosion score, evaluated by two blinded readers and one adjudicator for discordant cases (number of eroded joints ≤ three). Definition of eroded RX RA: EULAR 2013 Definition. In US, erosions were scored on six bilateral joints (MCP2-3, 5; MTP2-3, 5) with a four-grade scale. Results: A total of 168 patients were included: 122 RA (32 early RA < 2 years; 90 late RA ≥ 2 years); 46 OA patients. On RX: 42 RA patients (6 early; 36 late) and 5 OA patients have erosive diseases (sensitivity: 34.4%, specificity: 89.1%). On US, 95 RA patients (21 early; 78 late) and 12 OA patients have erosive diseases. Considering at least two joint facets eroded (threshold 1) or at least one joint facet eroded at grade 2 (threshold 2), sensitivities were good (68 and 72.1%), specificities excellent (89.1 and 100%). With only six targeted joint facets examined (6/30), sensitivities and specificities remained good (59.8 and 60.0%) and excellent (95.6 and 100%) with threshold 1 and 2 respectively. For all scenarios, agreement between RX and US for erosive RA was excellent ranged from 88.1% to 92.8%. Conclusion: US erosion assessment of six targeted joint facets detected 1.7 times more erosive RA patients than RX in late and early RA with good sensitivity and excellent specificity.